ANALISIS STRATEGI PENGEMBANGAN BISNIS BERDASARKAN PENGENDALIAN KUALITAS DAN PERSEDIAAN BARANG PADA PT. PASAR SWALAYAN MAJU BERSAMA - Deliyani Fang; Mario Andriaskiton (Journal Publicuho, 2022)
This study aims to describe the quality control and inventory of the business development strategy at PT. Pasar Swalayan Maju Bersama. The data used in this study is primary data taken using purposive where the data collection technique with certain considerations is the questionnaire method to 68 samples from 314 staff at PT. Pasar Swalayan Maju Bersama. The results of this study indicate that the variables of quality control, inventory have a significant effect on business development strategies. The result of the coefficient of determination in this study is 0.877 or 87% so that the variables of quality control and inventory can explain purchasing decisions of 87% and the remaining 13% are explained by other variables such as price and service quality.